Nutritional Evaluation of Quail-Based Complementary Food to Prevent Stunting in Early Childhood - Rosa, Mutya; Rahayuningsih, Mulyorini; Hambali, Erliza (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2025)
The quail, an endemic Indonesian poultry species, offers high nutritional value in its meat and eggs. The first 1,000 days of a child's life are crucial for optimal growth and development, with complementary foods as a key nutritional source. This study aimed to develop an instant quail-based complementary porridge enriched with various legumes. The research employed an experimental laboratory method complemented by quantitative nutritional analysis and organoleptic testing. Results indicated that the best formulation utilized soybeans, meeting the Indonesian National Standard (SNI) requirements for moisture, protein, and fat content. A 25-gram serving of the product contributes 37% of the recommended daily protein intake and provides 107 kcal of energy. The product qualifies for claims as a high-protein, high-fiber food rich in iron, vitamins, and minerals, demonstrating its potential to support infants' daily nutritional needs.